Probabilistic Surface Heat Flow Estimates Assimilating Paleoclimate History: New Implications for the Thermochemical Structure of Ireland - Mather, Ben; Farrell, Thomas; Fullea Urchulutegui, Javier (Journal of Geophysical Research: Solid Earth, 2018)
Regions where surface temperature has increased since past glaciation events, such as Ireland, underestimate the heat output of the Earth unless paleoclimate corrections are applied. We apply probabilistic techniques to quantify the uncertainty of 22 paleoclimate-corrected heat flow estimates in Ireland, which assimilate multiple surface temperature histories associated with 130ka of glacial oscillation in the British Isles. Heat flow values increase by approximate to 15mW/m(2) after a paleoclimate correction and provide new insights into the thermochemical structure of the lithosphere. The heat flow regime is broadly delineated by the Iapetus Suture Zone that separates Laurentian to the north and Avalonian terranes to the south (mean surface heat flow of 7314 and 6514mW/m(2), respectively). The degree to which heat-producing elements are partitioned into the uppermost crust is described by the differentiation index of a heat flow province. From Bayesian inversion, we determine that radiogenic elements are substantially more differentiated in the uppermost crust of Laurentia (D-I=2.81.4) than Avalonia (D-I=1.51.3), despite a moderately enriched lower crust (0.8 +/- 0.3W/m(3)). This is facilitated by a thin yet highly radiogenic layer in the uppermost crust of Laurentia (3.9 +/- 1.8W/m(3)). Extrapolating these results across the British Isles and Newfoundland suggests that heat-producing elements have been more successfully reworked into the upper crust to the north of the Iapetus Suture Zone during continental accretion between Laurentia and Avalonia. Irish Research Council for Science, Engineering and Technology Sustainable Energy Authority Of Ireland Comisión Europea Science Foundation Ireland Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub